An evaluation of teachers' perceptions of the new primary school curriculum in terms of some variables - Gokleksiz, Mehmet Nuri (Ani Yayincilik, 2007)
Problem Statement: Curriculum development studies have always been maintained since the founding of the Turkish Republic in order to create better teaching-learning environments as the result of continual changes. A new primary school curriculum was prepared and used in 120 pilot schools in nine cities as a pilot application in 2004. It is currently being used in all primary schools throughout Turkey. The new curriculum is based on the constructivist approach, active learning multiple intelligence and student-centered instruction. Teachers are the key persons in implementing a curriculum effectively. The success of a curriculum mostly depends on how teachers adopt and use it. Purpose of the Study: The purpose of the study is to determine the differences between the opinions of teachers about the implementation and effectiveness of the new curriculum in terms of class level, teaching experience and education level variables. Methods: A 24-item New Primary School Curriculum Scale, composed of four subscales, was used in this descriptive study. Validity and reliability of the scale was calculated. Cronbach Alpha reliability coefficient was found to be 0,92, KMO was measured to be 0,87 and Bartlett's test was calculated to be 1568,660. These results prove that data collection tool is valid and reliable. The scale was administered on 982 teachers in eight cities where the pilot curriculum was conducted. The findings of the study were evaluated in terms of class level, teaching experience and education level variables. The data were analyzed throughout one way ANOVA and Kruskall Wallis H tests. Findings and Results: No significant differences were found between the opinions of teachers on learning environment, knowing, adopting and implementing the curriculum and on the whole curriculum in terms of class and education level variables. A statistically significant difference was found between the opinions of the teachers on knowing the curriculum in terms of teaching experience variable but no significant difference was found on learning environment, adopting and implementing the curriculum and on the whole curriculum. Conclusions and Recommendations: The teachers should have in-service education about constructivism, multiple intelligence and student-centered instruction to implement the new curriculum effectively. Both theoretical information and practical examples should be introduced to the teachers. They should know the strong and weak sides of the new curriculum. The teacher-candidates should be taught the theoretical aspects of the new curriculum during their pre-service education.
Keywords: new primary school curriculum; curriculum evaluation; constructivism; student-centered instruction